Kampanye sosial dalam mengubah perilaku mahasiswa universitas dharma andalas terhadap sampah botol plastik di Instagram - Febriola Amanda Dewy; Indria Flowerina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2025)
This final project is based on the author's project during a social campaign titled "Social Campaign to Change the Behavior of Dharma Andalas University Students Towards Plastic Bottle Waste on Instagram." The issue of plastic bottle waste is an urgent environmental concern. Universities, as centers of education, play a vital role in shaping environmentally conscious student behavior. This social campaign aims to raise awareness among Dharma Andalas University students about the negative impacts of plastic bottle waste and encourage behavioral change towards using tumblers as a more environmentally friendly alternative. This campaign utilizes a visual communication approach through the TikTok and Instagram platforms. The author served as the creator of 1-minute advertising videos, encompassing the processes of filming and editing, designing banners and brochures, and actively participating in campaign activities for 60 days, from December 15th to February 15th. The campaign successfully increased student understanding of the plastic bottle waste issue and shifted their attitudes towards single-use plastic bottles, transitioning them to using tumblers. Challenges the author faced during the project included aligning creative ideas with the campaign's objectives and target audience. Production obstacles included limited resources, inadequate equipment, and tight schedules. Additionally, the editing process was time-consuming with repeated revisions. The process of synchronizing the voices of Mutiara and Rani in the conversation at 0:27-0:40 was particularly challenging to ensure accurate lip-sync. Once the video was completed, the next challenge was gaining viewership, especially among Dharma Andalas University students who may not all be connected through social media across different departments. After uploading, the advertisement video had to compete with thousands of other content pieces on the social media platforms.